RURAL AND LOCAL ECONOMIC DEVELOPMENT IN THE REGION FRUŠKA GORA – CASE STUDY - Pejanović, Radovan; Đukić, Sanja; Glavaš – Trbić, Danica (Economics of Agriculture, 2011)
Area of Fruska gora in recent decades had an inadequate development strategy. The project "Master Plan for Sustainable Development of Fruška gora 2012-2022." Defnes the region in the future as the area that will be the leader in regional development. Given the rural character of this area a priority in development planning is implementing the rural development. At the same time, rural development is sustainable at the local level, which emphasizes the importance of the concept of local economic development. Specifcs of Fruška gora require a detailed approach in development planning, as part of the region is entering the National Park "Fruška gora". Application of both models (rural and local economic development) are the most appropriate solutions for the formulation of development strategies for region Fruška gora, which was confrmed by the experience of EU countries using the LEADER program.